Mosquito home system: A case study of practical model to fight aedes in Kedah, Malaysia - Wan Aezwani, Wan Abu Bakar (2019)
INTRODUCTION: Dengue is a vector borne disease transmitted by Aedes mosquito. Preventing or reducing the virus transmission depends entirely on controlling the mosquito vectors. Transmission control activities should target Aedes in its immature stages (egg, larva and pupa) and adult stages in the household and immediate vicinity. This paper presents an alternative mechanism of combating this global disease by using an auto dissemination trap, called Mosquito Home System (MHS). METHODS: MHS is equipped with a special trade secret solution that is called as Insecticide Growth Regulator (IGR) is non-toxic, has a pheromone-like liquid formulation that is a chemical that serves to stimulate and have sexually attract the male and female that will attract and lure female mosquitoes to lay eggs in them, and will soon die after lying eggs. Those eggs that already laid with the chemical will not hatch or die at an expected 99% rate or go beyond the pulp level. This liquid prevents the food for the larvae into the water and in turn will kill the larvae. Once it lays eggs in the MHS, it kills the larvae and pulp in the new breeding ground. RESULTS: Data taken from October 2018 to April 2019 in Taman Ria, Sungai Petani, Kedah, Malaysia reveals that the decrease percentage of 82% on overall total number of Aedes eggs collected through MHS pots installed in that area. DISCUSSION: The MHS implementation in controlling dengue disease caused by Aedes mosquito could be enforced to the national and international level community.